Various Impregnation Methods Used for the Surface Modification of the Adsorbent: A Review - R. Girish, C.; ., . (International Journal of Engineering and Technology, 2018)
The water contamination is an important crisis which is to be addressed in the recent time. The pollutants present in wastewater are treated by adsorption using activated carbon, which is considered as one of the effective method. The adsorbent has to be modified to improve the adsorption capacity and the surface properties. Various methods such as physical, chemical treatment, impregnation and functionalization techniques are available. Impregnation is one of the effective method carried out for surface modification and to increase the adsorption capacity. Therefore, current study investigates the different impregnation methods used for the surface modification of the adsorbent. It also reviews the various precursors used for adsorbent preparation, the impregnating agent, the operating conditions and the adsorption capacity of the adsorbent.Â Â